2023
DOI: 10.1002/mp.16629
|View full text |Cite
|
Sign up to set email alerts
|

Localization of reference points in electromagnetic tracking data and their application for treatment error detection in interstitial breast brachytherapy

Abstract: BackgroundElectromagnetic tracking (EMT) is a promising technology that holds great potential to advance patient‐specific pre‐treatment verification in interstitial brachytherapy (iBT). It allows easy determination of the implant geometry without line‐of‐sight restrictions and without dose exposure to the patient. What it cannot provide, however, is a link to anatomical landmarks, such as the exit points of catheters or needles on the skin surface. These landmarks are required for the registration of EMT data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 50 publications
(113 reference statements)
0
4
0
Order By: Relevance
“…EMT is an elaborated tracking technology with the characteristic feature of accurate 3D position determination in the absence of a direct line-of -sight, which makes it particularly advantageous for clinical applications such as for the navigation of diagnostic and therapeutic procedures inside patients. Recently, the possibilities offered by EMT have attracted interest in the field of BT and various studies have shown promising results for tasks ranging from the detection of treatment errors 22,25,26 and uncertainties 20,23,24 to implant reconstruction. 28 In anticipation of a wider clinical application of EMT, a profound knowledge of the uncertainties associated with EMT in the context of BT are needed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…EMT is an elaborated tracking technology with the characteristic feature of accurate 3D position determination in the absence of a direct line-of -sight, which makes it particularly advantageous for clinical applications such as for the navigation of diagnostic and therapeutic procedures inside patients. Recently, the possibilities offered by EMT have attracted interest in the field of BT and various studies have shown promising results for tasks ranging from the detection of treatment errors 22,25,26 and uncertainties 20,23,24 to implant reconstruction. 28 In anticipation of a wider clinical application of EMT, a profound knowledge of the uncertainties associated with EMT in the context of BT are needed.…”
Section: Discussionmentioning
confidence: 99%
“…17 By integrating EMT functions into an afterloader and automatically driving the sensor through the BT applicator or implant, this so-called hybrid treatment delivery system allows assessment of the applicator/implant geometry inside the patient directly on the treatment table and without the need for other imaging techniques like CT, MRI, or US. [18][19][20][21] Various phantom and patient studies from different institutions have demonstrated that BT treatments benefit from the geometric information acquired by EMT, especially with respect to treatment error and uncertainty detection 20,[22][23][24][25][26][27] and automated applicator/implant reconstruction. [28][29][30][31] However, to establish EMT as an integral part of the clinical procedure, it must be ensured that the EMT system itself functions properly and achieves the necessary accuracy and precision.…”
Section: Introductionmentioning
confidence: 99%
“…for the same system 17 . A higher check cable speed would result in more outliers, due to a slight asynchronism of the timestamps of the EMT system compared to the afterloader device, according to Dürrbeck et al 22 …”
Section: Discussionmentioning
confidence: 99%
“…With an EMT‐equipped check cable, it is possible to determine the implant geometry in almost no extra time and without in‐room imaging facilities. The geometric information thus obtained is the basis for all applications of EMT in iBT, which range from catheter reconstruction 14,15 to error detection 16–18 and treatment verification 19–21 . A major drawback is that, unlike (cone‐beam) CT imaging, EMT cannot provide information about the anatomic context and hence about the target volume and the critical structures, without which the treatment plan quality cannot be appraised according to GEC‐ESTRO recommendations 11 .…”
Section: Introductionmentioning
confidence: 99%